Negative bureaucratic behavior in the Philippines the final report of the IDRC Philippine team - Cariño, Ledivina V.; De Guzman, Raul P. (1979)
This article integrates all the studies done by the College of Public Administration, University of the Philippines, regarding negative bureaucratic behavior, many of which appear on the earlier pages of this issue. Aside from providing convenient summaries, it analyzes the developmental implications-mostly negative--of graft and corruption across three types of governmental agencies. It also recommends policy towards more effective control of both individualized and systemic corruption through measures directed at the personnel, administrative culture, and politico-administrative and economic systems.
Keywords: Corruption; Corruption -- Government policy; Corruption -- Economic aspects; Government agencies -- Corrupt practices; Political corruption